Food hygiene and storage practices towards the understanding of food microbe among Universiti Malaysia Sabah (UMS) students - Mohammad Halim Jeinie; Norazmir Md Nor (University Putra Malaysia, 2022)
Lack of microbial knowledge among university students may expose them to food poisoning and disregard food safety concerns, especially food hygiene and storage practices. This research aimed to assess undergraduate students’ understanding of biological (microbial) food hazards and evaluate current food handling practices. The study involved 372 respondents consisting of UMS students, including Labuan and Sandakan campus branches. The respondents of this study consisted of students of different genders, ages, ethnicities, fields of study, years of study, faculties, and early studies. Respondents answered all 19 questions of the complete questionnaire, including demographics, personal hygiene practices, food storage practices, and microbial knowledge. Results: On average, the parts of personal hygiene, food storage practices, and microbial knowledge had values of (3.66 ± 0.414), (3.70 ± 0.363) and (3.52 ± 0.607), respectively. All variables showed a relationship categorised as moderate. The relationship between personal hygiene practices and knowledge was (r = 0.319), food storage practices and microbial knowledge were (r = 0.410), while personal hygiene practices and food storage practices were (r = 0.425). UMS students maintain a moderate level of knowledge on personal hygiene and food handling and have a level of knowledge on biological hazards (microbes) that affect food safety.